Using the Talking Stick Method in Learning Islamic Religious Education - Damayanti, Frischa; Bagheri, Mesbaholhoda; Sule, Muhammad Maga (Cahaya Ilmu Cendekia Publisher, 2023)
Purpose of the study: Can find out the process of using the Talking Stick method for learning Islamic Religious Education in parallel classes in junior high school. Apart from that, you can find out the obstacles and solutions to the process of using the Talking Stick method in learning Islamic Religious Education in parallel classes in junior high schools. Methodology: This research uses a qualitative approach where data collection techniques are carried out by means of observation, interviews and documentation, data analysis is carried out by means of data reduction, data presentation and drawing conclusions. Main Findings: The research results show that the process of using the Talking Stick method in learning Islamic Religious Education in parallel classes can run well, even though there are obstacles that can hinder the learning process. These include the schedule for Islamic religious education subjects starting at the last hour of learning, the lack of facilities that support the learning process, the time given to students to read and study the subject matter is only 20 minutes and using the Talking Stick method takes a very long time. when playing sticks. Novelty/Originality of this study: The implication of this research is that educators must be better able to use the Talking Stick method. To comply with the time specified in the learning implementation plan that has been made and so that learning runs according to what is expected. In learning, students need a lot of time to know and understand the lesson material given.